2022
DOI: 10.1007/s11064-022-03701-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differentially Alters Secretion of Brain Extracellular Vesicles During Aging: A Potential Mechanism for Maintaining Brain Homeostasis

Abstract: Extracellular vesicles (EVs) in the brain play a role in neuronal homeostasis by removing intracellular material and regulating cell-to-cell communication. Given that sex and aging differentially modulate brain networks, we investigated sex-dependent differences in EV levels and content in the brain during aging. EVs were isolated from the brains of 3, 6, 12, 18, and 24 month-old female and male C57BL/6 J mice, and the levels of different EV species determined. While the number of plasma membrane-derived micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…The hypothesis that mitovesicle exocytosis may act as a homeostatic mechanism to alleviate mitochondrial stress is consistent with earlier findings in other murine models of disease and physiological dysfunctions with mitochondrial abnormalities, including in aged mice when compared to younger counterparts (Kim et al., 2022). Furthermore, we previously found a similar correlation between brain hypometabolism, higher levels of mitovesicles, and a mitovesicle‐specific downregulation in ETC complex subunits in a mouse model of Down syndrome (D'Acunzo et al., 2021; Zammit et al., 2020), indicating a similar complex and generalised interconnection between intracellular and extracellular pathways involved in mitochondrial quality control when the homeostasis is altered, regardless of the source of the insult.…”
Section: Discussionsupporting
confidence: 90%
“…The hypothesis that mitovesicle exocytosis may act as a homeostatic mechanism to alleviate mitochondrial stress is consistent with earlier findings in other murine models of disease and physiological dysfunctions with mitochondrial abnormalities, including in aged mice when compared to younger counterparts (Kim et al., 2022). Furthermore, we previously found a similar correlation between brain hypometabolism, higher levels of mitovesicles, and a mitovesicle‐specific downregulation in ETC complex subunits in a mouse model of Down syndrome (D'Acunzo et al., 2021; Zammit et al., 2020), indicating a similar complex and generalised interconnection between intracellular and extracellular pathways involved in mitochondrial quality control when the homeostasis is altered, regardless of the source of the insult.…”
Section: Discussionsupporting
confidence: 90%
“…Their size is approximately 6 nm and differs from other subtypes of MDVs or EVs. Mitovesicles are small double-membrane EVs that contain proteins involved in catabolic pathway, energy production and pro-fission process, but lack of proteins involved in biosynthesis, transport and pro-fusion process [ 19 , 68 ]. Mechanisms of mitovesicles formation and release to extracellular space are not specified at this stage, but has been postulated to fuse with MVB before being secreted from the cells [ 68 ].…”
Section: Classification and Subtypes Of Mdvsmentioning
confidence: 99%
“…Moreover, immune regulation by MDVs has been emphasized in several reports of inflammation-associated diseases [ 3 , 12 , 14 ]. As such, MDVs have gained a wide interest in many mitochondria-associated disorders/diseases, such as cancers [ 15 , 16 ], aging [ 17 19 ], cardiovascular diseases [ 20 , 21 ], and neurodegenerative disorders [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, synovial exosome from joints have been found to express sex-specific patterns of miRNAs predictive of osteoarthritis [ 81 ]. A more recent study showed that there were sex differences in sub-cellular compartment protein representation in EVs derived from adult mouse brain [ 82 ]. Finally, in a recent study [ 83 ] that is pertinent to the outcomes of the current study, Baratta and colleagues documented sex differences in RNA content of EVs derived from whole brain of adult control mice, or mice exposed to alcohol.…”
Section: Discussionmentioning
confidence: 99%